Effect of Tinnitus and Duration of Deafness on Sound Localization and Speech Recognition in Noise in Patients With Single-Sided Deafness. (November 2018) - Liu, Yang-Wenyi; Cheng, Xiaoting; Chen, Bing; Peng, Kevin; Ishiyama, Akira; Fu, Qian-Jie
Patients with single-sided deafness (SSD) often experience poor sound localization, reduced speech understanding in noise, reduced quality of life, and tinnitus. The present study aims to evaluate effects of tinnitus and duration of deafness on sound localization and speech recognition in noise by SSD subjects. Sound localization and speech recognition in noise were measured in 26 SSD and 10 normal-hearing (NH) subjects. Speech was always presented directly in front of the listener. Noise was presented to the deaf ear, in front of the listener, or to the better hearing ear. Tinnitus severity was measured using visual analog scale and Tinnitus Handicap Inventory. Relative to NH subjects, SSD subjects had significant deficits in sound localization and speech recognition in all listening conditions ( p  < .001). For SSD subjects, speech recognition in noise was correlated with mean hearing thresholds in the better hearing ear ( p  < .001) but not in the deaf ear. SSD subjects with tinnitus performed poorer in sound localization and speech recognition in noise than those without tinnitus. Shorter duration of deafness was associated with greater tinnitus and sound localization difficulty. Tinnitus visual analog scale and Tinnitus Handicap Inventory were highly correlated; the degree of tinnitus was negatively correlated with sound localization and speech recognition in noise. Those experiencing noticeable tinnitus may benefit more from cochlear implantation than those without; subjective tinnitus reduction may be correlated with improved sound localization and speech recognition in noise. Subjects with longer duration of deafness demonstrated better sound localization, suggesting long-term compensation for loss of binaural cues.